The Influence of Countermovements on Inter-Segmental Coordination and Mechanical Energy Transfer during Vertical Jumping. Issue 5 (3rd September 2021) - Frayne, Devon H.; Zettel, John L.; Beach, Tyson A. C.; Brown, Stephen H. M.
Abstract: Inter-segmental coordination patterns and mechanical energy transfer were compared between vertical jumping tasks which possess different countermovement characteristics. Thirteen participants completed squat (SJ), countermovement (CMJ) and drop (DVJ) vertical jumps. Inter-segmental coordination patterns became more out-of-phase with increases in countermovement velocity (DVJ > CMJ > SJ), at the ankle, hip and lumbar spine (all p < 0.05), but not at the knee. With countermovements, more inter-segmental energy transfer occurred at all joints ( p < 0.05), but increasing the countermovement velocity (DVJ compared to CMJ) did not always increase energy transfer ( p < 0.001 for the hip and knee, p > 0.05 for the ankle and lumbar spine). The relationship between mechanical energy transfer and inter-segmental coordination patterns during vertical jumping is not straightforward since the responses to these varying countermovement demands were not consistent across all joints.